ANALYSIS OF VARIABLES ASSOCIATED WITH OVERWEIGHT AND OBESITY IN ITALIAN WORKERS (EuroMediterranean Biomedical Journal, 2026)
BACKGROUND: The present study aims to analyze variables related to overweight/ obesity in an Italian workers population, with particular attention to shift work.METHODS: This cross-sectional study analyzed the data retrieved from the "Aspects of daily life" survey, carried out by ISTAT in 2012.RESULTS: 16,725 participants (aged 18-64) met inclusion criteria; 44.28% of workers were overweight or obese (56.36% of males vs 27.24% of females, p64 yrs compared to younger colleagues: OR 4.02, 95% CI 2.91-5.58) as well as artisans compared to employees (OR 1.11, 95% CI 1.01 -1.23) and shift-work compared to daytime-work (OR 1.14, 95% CI 1.03-1.26). DISCUSSION: Our analysis in the Italian context is consistent with the existing knowledge, suggesting that overweight is significantly associated with shift work, even when controlling for important covariates, such as education, age, gender, civil status, BMI category.